Development and structural characterisation of gelatin-based sustainable food packaging from turkey (Meleagris gallopavo) skin by-product - Ozcan, Yilmaz; Kurt, Abdullah; Yildirim-Yalcin, Meral; Toker, Omer Said (WILEY, 2024)
In view of the environmental problems resulting from plastic-based packaging, gelatin film production from alternative, sustainable sources are extremely important. The objective of this study was to utilise a major source of collagen derived from poultry waste to produce and characterise turkey skin gelatin films (TGF). TGFs were produced at different glycerol concentrations (20%, 30% and 40%) via solvent casting technique. TGFs characteristics were also compared with the bovine gelatin films (BGF). The thermal structural development of TGF solutions to form a film network was not affected by the glycerol content in the temperature sweep test. This property was determined earlier and at higher temperatures in TGF (22 degrees C-23 degrees C) than in BGF (19 degrees C). As the glycerol ratio increased, the moisture content increased from 14.80% to 22.46%, while the thickness (36 mu m) and density (1.134-1.247 g cm(-3)) of TGFs remained constant due to the compact structures. The water vapour transmission rates of TGFs and BGF were similar (P >0.05), ranging from 0.48 to 0.53 g mm m(-2) h(-1) kPa(-1). Lower solubility was found for TGF20 (44.78%) and TGF30 (63.59%) films compared to BGF30 (63.59%). TGF20 exhibited the highest tensile strength and lowest elongation at break values. TGF40 and BGF30 demonstrated the highest flexibility and extensibility (P >0.05). In XRD analysis, TG40 demonstrated a less amorphous film structure compared to BG30, since the increased interaction due to glycerol provided a more ordered polymeric structure. TG20 and TG30 showed lower decomposition rates and higher residue levels, indicating their higher thermal stability. Thus, gelatin films based on turkey skin could be the alternative natural biodegradable films with suitable glycerol content for desired mechanical, barrier and thermal properties.
Keywords: Edible film; gelatin; glycerol; structural properties; turkey skin; FUNCTIONAL-PROPERTIES; PHYSICAL-PROPERTIES; EDIBLE FILMS; FISH GELATIN; MECHANICAL-PROPERTIES; SOY PROTEIN; PLASTICIZER; ANTIOXIDANT; OIL; Food Science & Technology